Tercentenary of Ars Conjectandi (1713): Jacob Bernoulli and the Founding of Mathematical Probability. (24th March 2014) - Sylla, Edith Dudley
Summary The Tercentenary of the publication of Jacob Bernoulli's Ars Conjectandi (The Art of Conjecturing) provides an opportunity to look at the origins of mathematical probability from Jacob Bernoulli's point of view. Bernoulli gave a mathematically rigorous proof of what has come to be called the weak law of large numbers, relevant to discovering ratios of unknown factors through sampling. The Art of Conjecturing was a bridge between the mathematics of expectation in games of chance as found in Huygens's On Reckoning in Games of Chance and mathematical probability as found in Abraham De Moivre's The Doctrine of Chances. This paper looks at the conceptual context as well as the mathematics of Bernoulli's book.